IS TANZANIA’S LOGISTICS INFLUENCE CHINA'S FOREIGN DIRECT INVESTMENTS?: A QUANTITATIVE APPRAISAL - Nuhu A. Sansa (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2020)
This study was conducted to evaluate the effect of the Tanzania Logistics on Chinese Foreign Direct Investment for the period 2007 to 2017 in Tanzania. The Simple Regression Model has been used to evaluate the Effects of Tanzania Logistics on Chinese Foreign Direct Investment over the period 2007 to 2017 in Tanzania. From world bank data and data published by author Han in 2019 the influence of Tanzania's logistics on Chinese foreign direct investment was analyzed in the 2007-2017 period in Tanzania. The findings of this study are quite interesting. Research findings reveal that there is a significant positive relationship between Tanzania Logistics and Chinese Foreign Direct Investment during the 2007 to 2017 period in Tanzania. The results showed that the Tanzania Logistics Affect the overall Chinese Foreign Direct Investment during the period 2007 to 2017 in Tanzania.